Isolation and Characterization of Microorganisms From Scoby (Symbiotic Culture of Bacteria and Yeast) During Kombucha Fermentation - Eva Yuliana; Anita Herawati Permana (Journal Warta AKAB, 2022)
Kombucha is made by fermenting tea with sugar solution using SCOBY (symbiotic culture of bacteria and yeast). Kombucha fermentation is divided into several stages, such as the conversion of sugar into ethanol, the conversion of ethanol into acetic acid, and the conversion of acetic acid into carbon dioxide. Thus, several types of unique microorganisms must be involved during kombucha fermentation. Our previous research has reported that culturable microorganisms from kombucha drink (liquid phase) were all bacteria. Furthermore, in this research we investigated culturable microorganisms from the SCOBY itself. During kombucha fermentation, SCOBY sheets were cut (about 1×1 cm) each day using a sterile knife. SCOBY slice was enriched in Potato Dextrose Broth and incubated at 37 °C for 24 hours. The enriched culture was inoculated into Plate Count Agar and incubated at 37 °C for 24 hours. Four different colonies, named isolate (a), (b), (c), (d), were collected during 14 days of kombucha fermentation. The suspected colonies of bacteria were cultivated in Nutrient Agar, while the suspected colonies of mold or yeast were cultivated in Potato Dextrose Agar. The characterization results suggested that isolate (a) has close characteristic to Acetobacter genus (gram negative, short rod, does not produce endospore), meanwhile isolate (b) is gram negative, long rod, and produces endospore. Isolate (c) was suspected as mold, and isolate (d) was identified as yeast.